Education Webinar Increaces The Knowledge of The Mask Waste Management During COVID-19 Pandemic - Situmorang, Anggia Gracia Marlina; Farahannisa, Kintan Adelia; Rahmawati, Iqlima; Rossyanti, Lynda (Journal of Community Medicine and Public Health Research, 2022)
Covid-19 caused many countries to implement new policies to combat its transmission. Among these new policies is the mandatory use of face masks in public spaces, which increased their production, consumption, and mask waste in the environment. Insufficient knowledge and awareness about the proper disposal of used masks, especially medical masks, might lead to environmental pollution due to microplastic particles and widespread contamination of Covid-19, which will affect sanitation and clean water supplies. Thus, providing education regarding proper and responsible masks use and disposal is essential to maintain good health for all and reduce potential environmental hazards amidst the Covid-19 pandemic. To understand the effect of providing education on knowledge regarding the use and management of medical masks,"EMISSION: Reducing Mask Waste in the Midst of Covid-19 Pandemic” webinar was conducted. This study used the One Group Pretest-post-test Design research method. The sample was selected by purposive sampling technique. The variable studied was the increase in knowledge as measured by pretest and post-test questionnaires. The obtained data were tested by using Paired Samples T-Test. There was a significant effect between knowledge scores related to medical masks before (pretest) and after the (post-test) webinar with a difference in the average value of 0.59 and p-value = 0.000. Education through "EMISSION: Reducing Mask Waste in the Midst of Covid-19 Pandemic" webinar increased public knowledge regarding medical masks to help ensure good health and well-being.